Characterization of metabolic and inflammatory responses following administration of three commercially available Mannheimia haemolytica vaccines to beef heifers - Colten W. Dornbach; Nicole C. Burdick Sanchez; Jacob Hagenmaier; Michael S. Brown; Jeff A. Carroll; Kristin E. Hales; Paul R. Broadway (Frontiers in Animal Science)
To evaluate the acute physiological and immunological responses to Mannheimia haemolytica vaccines, weaned heifers (n = 32; body weight [BW] = 296 ± 6.4 kg) were used in a completely randomized design. Heifers were balanced by BW and randomly assigned to one of three vaccine treatments: Nuplura PH (Elanco, Greenfield, IN; NP), OneShot (Zoetis, Parsippany, NJ; OS), or Presponse SQ (Boehringer Ingelheim, St. Joseph, MO; PS). Serial blood samples were collected for 7 d following vaccine administration to quantify multiple serum biomarkers and complete blood cell counts. Heifers were fitted with indwelling vaginal temperature recording devices for the duration of the study. No differences were noted in most CBC variables (P ≥ 0.27) except for PS heifers having greater lymphocytes (P = 0.02) and eosinophils (P < 0.01) than NP and OS heifers. Cortisol remained at or below basal concentrations for the duration of the study (P = 0.23). Glucose concentrations were greater for NP than OS, with PS being intermediate (P = 0.05). There was a tendency (P = 0.08) for a treatment × time interaction for circulating haptoglobin concentrations as NP heifers had a spike of greater magnitude but decreased duration. Likewise, a tendency (P = 0.07) was detected for decreased ceruloplasmin concentrations in PS heifers. The concentration of interleukin-6 (IL-6) was lesser in OS heifers than PS and NP heifers (P = 0.02), but PS heifers had decreased IL-4 concentrations (P < 0.01). No differences were observed in circulating interferon-gamma concentrations among treatments (P = 0.20). Overall, each vaccine treatment elicited similar physiological and inflammatory immune responses despite differences in vaccine composition. Although select immunological markers differed relative to vaccine treatment, it is unlikely these differences resulted in biologically relevant differences.